(untitled) (Global Journal of Science Frontier Research, 2021)
Recently, Aroramyces herrerae was described based on morphology, ecology, and taxonomically placed in the family Hysterangiaceae (Hysterangiales). However, a DNA analysis revealed that A. herrerae belongs to a new sequestrate cryptic genus, Pterosporomyces, in the family Trappeaceae (Phallales), nested with Restingomyces reticulatus and Phalobata alba and jointly forming a basal clade of Phallales with strong statistical support. Pterosporomyces herrerae gen. nov